ORGANISATIONAL CITIZENSHIP BEHAVIOUR GURU MADRASAH ISTIQLAL JAKARTA DITINJAU DARI STATUS PEGAWAI YAYASAN - Alwi, Muhamad (Almarhalah: Jurnal Pendidikan Islam, 2022)
Teachers play a very strategic role for the progress of a school institution. The teacher's role is multidimensional and graded according to education level, namely as: educator, teacher, leader, servant, mentor, motivator, and researcher. Therefore, the behavior of Organization Citizenship Behavior (OCB) should be owned by educators, especially teachers. Individual behavior in the organization is distinguished into behavior that is in accordance with the role (intra-role behavior) and behavior outside or beyond the role (extra-role behavior). Extra role itself has many terms, one of which is Organizational Citizenship Behavior (OCB). Organization Citizenship Behavior (OCB) is a positive work behavior, outside of the tasks imposed by the organization carried out by a teacher. This study uses quantitative research methods, with the number of research subjects totaling 94 teachers of Madrasah Istiqlal Jakarta (MIJ), both teachers with permanent foundation teachers (GTY) and non-permanent Foundation teachers (GTTY). The research instrument used is the OCB scale. The scale is compiled using Likert scale modeling. The results showed that based on the OCB frequency distribution of permanent teachers at the Jakarta Istiqlal Madrasah Foundation above, the research subject data showed that there were 6 teachers or 11.11% who had a very high OCB level, 31 teachers or 57.41% had a very high OCB. high, 13 teachers or 24.07 low OCB levels, and 4 teachers or 7.41. While the OCB frequency distribution for non-permanent foundation teachers is 8 teachers or 20% have very high OCB levels, 24 teachers or 60% high OCB levels, 5 teachers or 12.50% low OCB levels, and 3 teachers or 7.50%.